Kadar Kolesterol Darah Total Pada Pasien Rawat Jalan Laki – Laki Usia 40 Sampai Dengan 70 Tahun Di Rumah Sakit TNI AU LANUD Sam Ratulangi Manado - Augustinus Robin Butarbutar (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2023)
The type of fat that is best known by parents or the public that can cause disease is cholesterol. According to Yogendra Kumar, 2021, normal total cholesterol levels in the blood are in the range of 140-200 mg/dl, while high total cholesterol levels are between 200-400 mg/dl. Men aged 40 years and over with high serum cholesterol levels, namely cholesterol > 200 mg/dL and LDL cholesterol > 130 mg/dL, have a high risk of stroke and coronary heart disease (CHD). Based on WHO data for 2015, Yusvita and Shinta (2018) reported that globally there were 17.7 million deaths due to heart and blood vessel disease. Data collection was carried out based on the results of blood cholesterol examination in every man aged 40 to 70 years. This research approach is descriptive. The samples taken amounted to 30 people according to the criteria and are willing to be respondents. This research method uses total sampling. From the results of the study it was found that high total cholesterol levels were > 200 mg/dl at ages 40-55 years with 6 respondents out of 12, while those aged 56-70 years only amounted to 4 respondents out of 8. This shows that the percentage of ages 40-55 and 56-70 is not much different or the same. Total blood cholesterol levels in men aged 40 years to 70 years have normal values ​​or > 200 mg/dl with a percentage of 60% and 40% having high value or > 200 mg/dl from 30 respondents or outpatients who were sampled . High total blood cholesterol levels or > 200 mg/dl have a risk of stroke and coronary heart disease, while normal total blood cholesterol levels or < 200 mg/dl have a low risk. This basic research is expected to be a reference for further or other research and can be useful for readers, especially men aged 40 to 70 years.